Modeling of in vitro drug release from polymeric microparticle carriers - Djekić, Ljiljana; Ćirić, Ana (Archives of Pharmacy, 2022)
Incorporation of active substances in polymer microparticles (microencapsulation) is important technological strategy used in pharmaceutical industry to improve quality, safety and/or therapeutic efficiency of pharmaceutical preparations for different routes of administration. The current focus is on encapsulation of small molecules and macromolecules into microparticles based on biocompatible synthetic polymers and biopolymers, such as polypeptides and polysaccharides, in order to achieve preferable drug release kinetics. Diversity in microparticle structure and size, choice of polymers, and manufacturing processes, allows designing of a multitude of microcarriers (e.g., monolithic matrix microspheres, hollow microcapsules, water- or oil-core microcapsules, stimulus-sensitive microcapsules), whereby their impact on biopharmaceutical profile of drugs can be manipulated. The results so far indicate that the in vitro drug release kinetics evaluation is one of the key aspects of the microparticle-type carrier characterization, where the application of the mathematical analysis of release profiles is an important tool for elucidating drug release mechanisms as well as for evaluating the influence and optimization of formulation and process parameters in microencapsulation procedure. The article reviews representative studies in which mathematical modeling of experimentally obtained release data was performed for microencapsulated model drugs with different physicochemical properties, as well as significance and potential limitations of this approach.